Sustainable assessment of ultrasound-assisted extraction of anthocyanins with bio-based solvents for upgrading grape pomace Cabernet Sauvignon derived from a winemaking process - Andrés Córdova; Sebastián Catalán; Vinka Carrasco; Fabiane O. Farias; Julia Trentin; Jessica López; Fernando Salazar; Cassamo U. Mussagy (Ultrasonics Sonochemistry)
This work assessed the efficiency and sustainability of ultrasound-assisted extraction (UAE) of anthocyanins from grape pomace using bio-based solvents: Ethanol, Isopropanol, Propylene-glycol, and Ethylene-glycol at different concentrations (50 and 100 % v/v) and temperatures (25 °C and 50 °C). Higher ultrasonic intensities (UI) were obtained at 50 °C and 50 % v/v by decreasing solvents viscosities. Under these conditions, anthocyanin extractions were performed with different combinations of solvent to liquid ratio (SLR) at 1:10 and 1:50 g/mL, and UI (3.9 and 13.9 W/cm2). Samples were taken from 0 to 40 min. Ultrasound induced a fast extraction of anthocyanins: a plateau was reached at 5 min and the continuation of the sonication only provoked a marginal increase which is transferred in lower Productivity (Pr) rand higher energy consumptions. The COSMO-SAC model validated solute–solvent interactions, providing robust predictive insights where ethanol showed the highest anthocyanin extraction and productivities (1.094 kg/hL). However, propylene-glycol showed the highest eco-scale scores (∼ 80) within the range defined as “Excellent” and antioxidant capacity (2758.34 ± 6.26 μmol TE/g DM) regardless of the UI, and with very low energy consumption when the extraction was performed at 3.9 W/cm2 and SLR of 1:10 g/mL. These results show that integration of UAE and bio-based solvents presented a sustainable and efficient method for valorizing wine making by-products, with significant improvements with respect to the conventional extraction, thus promoting eco-friendly practices for the food industry, and supporting the circular economy.